Physics: Frightful, but fun. Pupils' and teachers' views of physics and physics teaching - Angell, Carl; Guttersrud, Øystein; Henriksen, Ellen K; Isnes, Anders (Science education (Salem, Mass.), 2004)
There is widespread concern for the situation of school physics regarding recruitment, contents, teaching methods, etc. In this study based on questionnaire and focus group data, we explore how upper secondary pupils and teachers perceive physics as a subject, how they experience physics instruction, and how physics compares to other subjects.Our study shows that pupils find physics interesting, but difficult and work-intensive; formalistic in nature, but still describing the world and everyday phenomena. Pupils express that exoti topics like astrophysics are closer to their life-world than mechanics etc. Whereas teachers complain about pupils' poor mathematics skills, pupils do not see this as a major problem. Physics instruction is still dominated by traditional content knowledge and seems to attract and reward pupils with this orientation. Pupils have a relatively weak understanding of the central role of experiments in science. Generally, pupils appear conservative in their views on teaching and learning; however, they would like stronger emphasis on qualitative and pupil-centred approaches.Based on our findings, we suggest that an upper secondary physics education preparing pupils for tomorrow's society should be characterized by variety, both within and among courses, integration of mathematics in the physics courses, more pupil-centred instruction, and a stronger emphasis on knowledge in context.